Le nanoscienze approdano alla Scuola Segre (e alla Scuola Del Re) con un mare di opportunità didattiche, ma anche di sfide da affrontare - Venturi, Margherita (Chimica nella Scuola, 2022)
In 2021 the Didactics Division of the Italian Chemical Society decided to jointly start the “Ulderico Segre” School of Educational Research and Chemistry Didactics, mainly dedicated to university teachers, and the National School of Chemistry Education “Giuseppe Del Re”, mainly involving the teachers of the secondary school, for the following reason: since the chosen theme, nanosciences, due to its increasing importance in the field of application, begins to have significant impact in chemical teaching at all levels of education, we wanted to favor and maximize the interaction between all the actors involved in the teaching/learning process of Chemistry. After two common days, however, the Segre School and the Del Re School “separated”; in fact, for each, two further days were organized with activities selected ad hoc considering the different target of the schools. This contribution contains a brief report of the two introductory days, while the one published below describes what was dealt with in the days dedicated specifically to the Segre School.